2010
DOI: 10.3199/iscb.5.87
|View full text |Cite
|
Sign up to set email alerts
|

A cytogenetic study in three species of Achillea

Abstract: ABSTRACT.To make research cytogenetic properties of commonly distributed species in East Eurasian Flora related to Flora of Japan, the chromosome numbers and karyotypes in two species and one subspecies of Achillea in Japan and Russia were investigated by orcein and fl uorescent sequential staining of GC-specifi c chromomycin A 3 (CMA) and AT-specifi c 4', 6-diamidino-2-phenylindole (DAPI) banding methods. Achillea alpina subsp. subcartilaginea, A. asiatica and A. millefolium showed the tetraploidal and hexapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
2
1
1
Order By: Relevance
“…Our results were consistent with those of a report by Sahin et al (Sahin et al, 2006). On the contrary, no satellites were reported in certain studies (Afshari et al, 2013;Chehregani & Javaheri, 2014;Kiran et al, 2012) whereas one to three satellites have been reported in some other researches (Afshari et al, 2013;Hoshi et al, 2010). Additionally, more satellites were observed in submetacentric chromosomes and the results were consistent with those of the present study (Hoshi et al, 2010).…”
Section: Discussionsupporting
confidence: 94%
“…Our results were consistent with those of a report by Sahin et al (Sahin et al, 2006). On the contrary, no satellites were reported in certain studies (Afshari et al, 2013;Chehregani & Javaheri, 2014;Kiran et al, 2012) whereas one to three satellites have been reported in some other researches (Afshari et al, 2013;Hoshi et al, 2010). Additionally, more satellites were observed in submetacentric chromosomes and the results were consistent with those of the present study (Hoshi et al, 2010).…”
Section: Discussionsupporting
confidence: 94%
“…Our results were consistent with those of a report by Sahin et al ( 2006). On the contrary, no satellites were reported in certain studies ( Hoshi et al 2010, Kiran et al 2012, Afshari et al 2013 Javaheri 2014) whereas one to three satellites have been reported in some other researches (Afshari et al 2013). Additionally, more satellites were observed in submetacentric chromosomes and the results were consistent with those of the present study (Hoshi et al 2010).…”
Section: Discussionsupporting
confidence: 93%
“…In addition to inter-species diversity in ploidy levels, there are numerous reports of ploidy level diversity in populations within a species. In other words, different ploidy levels are reported for populations of a species ( Hoshi et al 2010, Ebrahim et al 2012. Accordingly, a range between diploid to hexaploidy has been reported for A. aleppica species (Rad and Javaheri 2014); however, all the accessions of the species were diploid in the present study.…”
Section: Discussioncontrasting
confidence: 67%
“…The karyology of the genus has been studied by several researchers and reported chromosome numbers included 2n=18, 36, 54 and 72 (Lawrence 1947;Contandriopoulos and Martin 1967;Löve 1972Löve , 1973Androschchuk and Kostinenko 1981; Rotreklova 2000, 2001;Constantinidis and Kalpotzakis 2005;Kiran et al 2008;Kondo 1998;Hoshi et al 2010), only a few chromosome reports have been published on the genus in Iran (Chehregani and Mehanfar 2008;Sheidai et al 2009;Farsi et al 2002). These indicated that the chromosome numbers and chromosome morphology were unknown for many Achillea species in Iran.…”
Section: Introductionmentioning
confidence: 99%